2018
DOI: 10.1002/ptr.6191
|View full text |Cite
|
Sign up to set email alerts
|

Antiallodynic effect induced by [6]‐gingerol in neuropathic rats is mediated by activation of the serotoninergic system and the nitric oxide–cyclic guanosine monophosphate–adenosine triphosphate‐sensitive K+ channel pathway

Abstract: The present study evaluated the possible antiallodynic effect induced by [6]-gingerol in rats with L5-L6 spinal nerve ligation (SNL). Moreover, we determined the possible mechanism underlying the antiallodynic effect induced by [6]-gingerol in neuropathic rats. The animals underwent L5-L6 SNL for the purpose of developing tactile allodynia. Tactile allodynia was measured with von Frey filaments. Intrathecal administration of [6]-gingerol reversed SNL-induced tactile allodynia. The [6]-gingerolinduced antiallod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…All experiments were performed on female Wistar rats weighing 140-160 g (n = 162). Previous studies have demonstrated no difference in tactile allodynia between female and male rats in the SNL model [23,28,29]. For this reason, we decided to use female rat in this study.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…All experiments were performed on female Wistar rats weighing 140-160 g (n = 162). Previous studies have demonstrated no difference in tactile allodynia between female and male rats in the SNL model [23,28,29]. For this reason, we decided to use female rat in this study.…”
Section: Animalsmentioning
confidence: 99%
“…Other studies have reported that drugs which activate the NO-cGMP pathway seem to modulate the opening of the K + channels in order to produce nociception [20]. Previous studies have indicated that natural products produce anti-nociceptive and anti-allodynic effects through the NO-cGMP-ATP sensitive channels K + pathway [20][21][22][23][24][25][26]. There is evidence that suggests that curcumin exhibits its anti-nociceptive effect by directly stimulating K + ATP channels in an inflammatory pain model [27].…”
mentioning
confidence: 99%
“…Moreover, 6-gingerol attenuated acetic acid-induced writhing response and formalin-induced pain (Young et al, 2005). Preclinical studies subsequently provided evidence for the therapeutic effect of 6-gingerol in rats with L5-L6 spinal nerve ligation (Mata-Bermudez, Izquierdo, de los Monteros-Zuñiga, Coen, & Godínez-Chaparro, 2018).…”
Section: Experimental Pharmacologymentioning
confidence: 96%
“…The antiallodynic effect induced by intrathecal administration of 6-gingerol was mediated, at least in part, by the NO-cGMP-ATPsensitive K+ channel pathways and by the serotoninergic system via activation of 5-HT A/1B/1D/1F (Mata-Bermudez et al, 2018).…”
Section: Experimental Pharmacologymentioning
confidence: 96%
See 1 more Smart Citation